Durability Study Of Precast Concrete Sandwich Panel Under Exposure To Sea Water - Ahmad, Aftab (2002)
An experimental investigation was conducted to observe and study the behavior of precast concrete sandwich panels in corrosive environment of chloride ion in marine environment. Three different strengths of marine waters were prepared namely one time, three time and six times of the concentration of actual ocean water. Twenty-seven numbers of sandwich panels were casted and nine numbers were placed in each types of solution. Along with that one number of Panel was casted to use as control specimen and left in air for eight months .Two more sandwich panel were used for permeability tests. The study deals with the experimental investigation of panels for their ability to stand in corrosive environment and probability of corrosion in panel reinforcement. The results obtained were analyzed and observation was made to identify the corrosion probability, location of maximum corrosion and corrosion rate of the sandwich panel reinforcement. Comparative behaviors of the concrete strength variation in different chloride environment were observed. From the observation of the experimental results it was found that at higher chloride concentration in the environment causes higher corrosion and in the same environment highest corrosion was found along the edges of the precast concrete sandwich panel. There was no critical loss of concrete strength in sandwich panel due to submersion test.